Development Learning Devices To Improve Student’s Mathematical Literations - Rick Hunter Simanungkalit; Hardi Suyitno; Isnarto Isnarto; Dwijanto Dwijanto (International Conference on Science, Education, and Technology, 2021)
The purpose of this study was to determine: (1) how to develop valid problem-based learning-oriented learning devices, (2) how to develop practical problem-based learning-oriented learning devices, (3) how to develop effective problem-based learning-oriented learning devices, and (4) whether applying problem-based learning-oriented learning devicescan improve students' mathematical literacy skills. This research is a development research using the Thiagarajan development model, namely the modified 4D (Define, Design, Develop and Disseminate) model. The learning devicesdeveloped were lesson plans, student activity sheets, student books, and students' mathematical literacy test instruments. The research instruments were: (a) validation sheets for learning devicesincluding: lesson plans, student activity sheets, student books and tests of mathematical literacy skills; (b) the observation sheet to see the teacher's ability to manage student learning and activities; (c) a research questionnaire to see student responses to learning. The results of data analysis indicate that the learning devicesdeveloped are oriented toward problem-based learning that meet the criteria of validity, practicality and effectiveness. There was an increase in students' mathematical literacy skills using the developed learning devices.